Consumption of edible oil blended with flax, coconut, sunflower, and olive oil can significantly improve the negative health consequences of high-fat/high-cholesterol diet in Sprague Dawley rats - Rabail, Roshina; Altemimi, Ammar B.; Maerescu, Cristina Maria; Socol, Claudia Terezia; Criste, Florin Leontin; Khalid, Abdur Rauf; Mahwish; Hussain, Shahzad; Liu, Zhi-Wei; Aadil, Rana Muhammad (Frontiers in Nutrition, 2024)
Increasing cardiac, hepatic, and metabolic diseases have raised the need to modify our contemporary lifestyles towards' balancing and diversifying the nutrients in our daily diet.Especially the dietary fats should be modified to healthier versions by blending different vegetable oils. Thereby, in this study an oil blend with health protective and promotive fatty acid combinations was investigated to bring down the progression of cardiac and other metabolic diseases. A bio-efficacy trial was performed to investigate the therapeutic potential of an oil blend in 30 hyperlipidemic rats. Five rats were allocated to each group (coconut, flaxseed, olive, sunflower, and blended oil) for 42 days and were compared with initial values of hyperlipidemic rats. Methodological investigations were performed for the body weight, naso-anal length, various obesity indices, visceral fat accumulation, blood and serum, cardiovascular risk indices, and echocardiograph. On comparison to the initial values there were significant reductions of 53.12% in body fat content (3.98±0.96), 6.82% in Lee index (289.60±8.27), 16.84% in BMI (0.15±0.003), 57.37% in total cholesterol (52.00±9.03), 68.57% in triacylglycerides (99.00±9.19), 61.16% in atherogenic index (0.88±0.12), and 58.72% in coronary risk index (2.88± 0.12). These results indicated that the blended oil consumption has significantly reduced various obesity indices, improved lipid profile, and provided significant protection against cardiovascular risk indices. Moreover, the results of blended oil indicated significant health protective ameliorations in electrocardiograph. Its regular consumption could help to reduce the onset of obesity and metabolic diseases.